Chiral glutamic acid functionalized graphene: preparation and application. Issue 13 (10th June 2015) - Han, Qian; Xia, Qiao; Guo, Dongmei; Li, Can; Fu, Yingzi
Abstract : l -glutamic acid andd -glutamic acid were covalently grafted onto graphene sheets via the amide formation between amino groups of glutamic acid enantiomers and oxygen-containing groups in graphene oxide. The resultant hybrids have high chiral properties and excellent electrochemical activity towards electroactive 3, 4-dihydroxyphenylalanine (DOPA) enantiomers. Abstract : Through the amide group of glutamic acid enantiomer and oxygen-containing groups in graphene oxide, chiral functionalized graphene nanosheets were synthesized, which showed good enantioselective recognition of 3, 4-dihydroxyphenylalanine enantiomers. These chiral graphene hybrids should be novel promising materials for biological and pharmacological applications.